Controlling collective rotational patterns of magnetic rotors - Daiki Matsunaga (Nature Portfolio, 2019)
A challenge of magnetically-actuated devices is to obtain different behaviours from each component under the same driving field. Here the authors tune the dipolar interactions between rotors to obtain different rotational behaviours when actuated by a magnetic field leading to complex collective dynamics.